Levels of infection by gastrointestinal parasites of sire and theirs daughters as criteria for selection of helminth resistant sheep - Morales-Contreras, Gustavo Adolfo; Sandoval, Espartaco; Pino de Morales, Luz Arelis; Morales, Jairo; Jiménez, Delia (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The relationship between levels of infection with gastrointestinal nematodes expressed in eggs per gram counts (e.p.g) and categorized as negative, light, moderate and heavy, were analyzed by multivariate analysis of simple linear correspondence and the following results were obtained: The Bergamasca´s daughters were associated with light to moderate level of infection, while in the case of the Barbados Black Belly 1 (BBN 1) daughters, it was found an association with a negative level of infection. The daughters of the Barbados Black Belly 2 (BBN 2) were associated with heavy level of infection. When analyzing each sire breed with their infection levels, it was found that: the Bergamasca sire was associated with a moderate levels of infection, while the Barbados Black Belly 1 (BBN 1) showed infections levels oscillating from light to moderate. The sire Barbados Black Belly 2 (BBN 2) showed a good correspondence with heavy levels of infection. In conclusion, knowing the e.p.g count is a phenotypic expression of resistance to parasitic gastrointestinal infection, that is genetic in nature and therefore heritable. the selection of sire Barbados Black Belly 1(BBN 1) is discussed and proposed. The sire with the highest capacity Helminth Resistant was the BBN1